Day-to-day reliability of gait characteristics in rats. (27th April 2018) - Raffalt, Peter C.; Nielsen, Louise R.; Madsen, Stefan; Munk Højberg, Laurits; Pingel, Jessica; Nielsen, Jens Bo; Wienecke, Jacob; Alkjær, Tine
Abstract: The purpose of the present study was to determine the day-to-day reliability in stride characteristics in rats during treadmill walking obtained with two-dimensional (2D) motion capture. Kinematics were recorded from 26 adult rats during walking at 8 m/min, 12 m/min and 16 m/min on two separate days. Stride length, stride time, contact time, swing time and hip, knee and ankle joint range of motion were extracted from 15 strides. The relative reliability was assessed using intra-class correlation coefficients (ICC(1, 1)) and (ICC(3, 1)). The absolute reliability was determined using measurement error (ME). Across walking speeds, the relative reliability ranged from fair to good (ICCs between 0.4 and 0.75). The ME was below 91 mm for strides lengths, below 55 ms for the temporal stride variables and below 6.4° for the joint angle range of motion. In general, the results indicated an acceptable day-to-day reliability of the gait pattern parameters observed in rats during treadmill walking. The results of the present study may serve as a reference material that can help future intervention studies on rat gait characteristics both with respect to the selection of outcome measures and in the interpretation of the results.